2013
DOI: 10.1007/s00264-013-2090-3
|View full text |Cite
|
Sign up to set email alerts
|

Posterior acetabular arc angle of unstable posterior hip fracture–dislocation

Abstract: Purpose Posterior hip fracture-dislocation needs stability evaluation. A previous study in the normal acetabulum has shown that the coronal posterior acetabular arc angle (PAAA) could be used to assess an unstable posterior hip fracture. Our study was designed to assess PAAA of unstable posterior hip fracture-dislocation and whether posterior acetabular wall fracture involves the superior acetabular dome. Methods Using coronal computed tomography (CT) of the acetabulum and 3D reconstruction of the lateral pelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Preoperative assessment of posterior hip fracture dislocations is important in terms of planning treatment but difficult due to the complicated anatomicalstructure (9). After these injuries there are many factors affecting outcomes (14,15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preoperative assessment of posterior hip fracture dislocations is important in terms of planning treatment but difficult due to the complicated anatomicalstructure (9). After these injuries there are many factors affecting outcomes (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…In our cases, the acetabular defect percentage was determined to be minimum 39% and all hips were unstable and were patients admitted to the emergency service with hip fracture dislocations. Harnroongroj et al reported that in addition to this assessment, coronal PAAA values were beneficial to predict stability without requiring assessment of the normal hip (8,9). Investigations by Harnroongroj et al found coronal PAAA values of more than 77 degrees instable hips, while hips with less than 50 degrees were unstable (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this level, the fracture included part of posterior acetabular wall and position of femoral head is high degrees of flexion, the fracture mostly creates posterior acetabular wall fracture and dislocation hip. 4 62° of posterior acetabular roof arc angle of Chuckpaiwong and Harnroongroj included posterior end of anatomic superior articular cartilage of acetabulum because the transverse osteotomy started from greater sciatic notch passing through juxtatectal area of acetabulum and excluding posterior acetabular wall by the osteotomy. Moreover, the 62° posterior acetabular roof arc angle had confirmed no involvement of posterior portion of the ABSAWBA in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Acetabular fracture involving superior weight bearing area shows significantly poor results 12. Moreover, stability of the hip depends on adequate acetabular coverage of the femoral head 34. Roof arc angle is a method to evaluate adequate acetabular coverage and stability of the femoral head, Matta and Merritt study based on clinical findings and suggested that the fracture crosses acetabular weight bearing dome when <45° medial, anterior and posterior roof arc angles 56.…”
Section: Introductionmentioning
confidence: 99%